Ways and Means of Overcoming Lexical and Grammatical Difficulties in Passing the Test on RFL (Level B2) (Proceedings of Southern Federal University. Philology, 2020)
The article deals with the preparation of foreign students for RFL level B2 in order to form their communicative abilities in all spheres of communication. Attention to this issue is justified by the need to increase the productivity of studying Russian as a foreign language for bachelor’s degree, master’s degree, and even for admission to graduate school in the Humanities, engineering and natural sciences.Key words: RFL, vocabulary, grammar, verb, participle, adverb, complex sentence.DOI 10.18522/1995-0640-2020-1-182-189